Desenvolvimento de modelos de falhas em redutores de engrenagens para diagnóstico via observadores de estado - Firme, Tiago Bernardes [UNESP] (2014)
The increased competition among companies have demanded higher operating speeds and shorter periods of maintenance of equipment, for this reason it is extremely important to be able to extend equipment life through the prediction of potential failures . The objective of this project is to develop a methodology that enables to predict component failures of rotating systems. In numerical simulation, failures are identified by varying the RMS value of the velocity signal system, and quantification of failure made from the minimization of the norm the error between the data measured and robust observer. A gear reducer is designed to validate the method, the model was constructed and identified the unknown parameters, with the use of state observers the degrees of freedom were estimated, and a database RMS values, without fail, was developed to serve as a basis for comparison. With the inclusion of damage to the system through the base values, it was possible to identify the damage and the use of robust observer to quantify and locate the damage in the system even in the presence of noise